Long non-coding RNAs CCAT1 and CCAT2 in colorectal liver metastases are tumor-suppressive via MYC interaction and might predict patient outcomes - Franz, Clemens; Wührl, Michael; Hartmann, Sibylle; Klupp, Fee; Schmidt, Thomas; Schneider, Martin (PLOS ONE, 2023)
Background Liver metastases severely reduce the long term survival of colorectal cancer patients. Long non-coding RNAs (lncRNAs) CCAT1 and CCAT2 have previously been found to be associated with impaired patient outcomes in primary colorectal cancer. We aimed to elucidate the role of CCAT1 and CCAT2 in colorectal liver metastases. Methods Total RNA was isolated from 97 human tissue samples of colorectal liver metastases and adjacent normal liver tissue. Gene expression analysis was performed by RT-qPCR and Multiplex ELISA and correlated with patient characteristics and survival. Gene expression, cancer cell migration, invasion, and proliferation were studied after siRNA-mediated knockdown of CCAT1, CCAT2, and MYC in metastatic colorectal cancer cell lines Colo205 and HROC277Met2. Results Elevated expression levels of lncRNAs CCAT1 and CCAT2, and their common target MYC in colorectal liver metastases were associated with prolonged progression-free survival after liver resection. High expression of CCAT1 was likewise associated with prolonged overall survival. Knockdown of CCAT1, CCAT2, and MYC resulted in increased migratory and invasive potential in metastatic colorectal cancer cell lines. Gene expression analysis revealed alterations in constituents of Wnt signaling following knockdown. Conclusion Our findings demonstrate tumor-suppressive functions of lncRNAs CCAT1 and CCAT2 in colorectal liver metastases. They suppress Wnt signaling directly and indirectly through target gene MYC and might prevent further metastatic spread from colorectal liver metastases.